IMPLEMENTATION OF PROMOTIONAL MIX TO INCREASE THE NUMBER OF CUSTOMERS AND HOME BUSINESS INCOME DURING PANDEMIC COVID 19 - Nike Norma Epriliyana; Hari Budi Lestari; Nursamsida Tohari (MBA - Journal of Management and Business Aplication, 2022)
This research is inspired by the increasing number of creative actions carried out by homebusiness people who have to maintain their business income during the pandemic. Thiscreativity appears, to increase the number of customers in order to increase home businessincome. Finally, some home businesses develop their business by promoting their productsthrough online media, such as social media, collaboration with online distributors, givingdiscount, or promotion through WAG. This study aims to analyze the effect of implementing apromotional mix on increasing the number of customers and home business income during thepandemic. This research applies quantitative research. The respondents are 35 home businessesspread over 3 (three) Regencies. The data collection technique used a questionnaire sent viagoogleform. Data analysis using Path Analysis with SPSS ver. 22.00. The sampling techniqueusing random sampling with exogenous variables is the promotional mix implementation (X);exogenous variable is income (Y); and the intervening variable is the number of customers (Z).The results of the study conclude that (1) the variable of the promotional mix implementationhas a significant effect on increasing the number of customers as evidenced by the value of sig.0.000; and the value of 0.447; (2) the variable number of customers has a significant effect onrevenue as evidenced by the value of sig. 0.000; and the value of 0.545; (3) the implementationvariable of the promotional mix has no significant effect on revenue as evidenced by the valueof sig. 0.433.Keywords: Promotional Mix; Number of customers; Income